PENGARUH, PERTUMBUHAN PERUSAHAAN, DAN KEBIJAKAN DEVIDEN TERHADAP KEBIJAKAN HUTANG PERUSAHAAN (Studi Empiris pada Perusahaan Manufaktur Bidang Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2016) - Wenang Joko Pitono; Titin Arlinah (Sekolah Tinggi Manajemen IMMI Jakarta, 2020)
This research is intended to be published Institutional, Company approval, and Dividend Policy on Company Debt Policy towards manufacturing companies approved on the Indonesia Stock Exchange. The period used in this study is 5 (five) years, starting from 2012 to 2016.This research uses quantitative methods. The sample in this study was obtained by purposive sampling method. Based on the existing criteria, obtained 13 companies that became the study sample. The data analysis technique used is multiple linear regression.Based on the results of data analysis, Institutional Ownership does not conflict with company lending policies as evidenced by a coefficient value of -0.095 at a significance value of 0.445. It is expected that the Company does not oppose a loan policy as evidenced by a coefficient value of 0,000 at a significance value of 0.998. Dividend policy determines the company's debt policy as evidenced by a coefficient value of 0.324 at a significance value of 0.007. Simultaneously Institutional Ownership, Company approval, and Dividend Policy are against the Debt Policy, this is evidenced by the calculated F value of 2.688 at a significance value of 0.054. The multiple linear regression equation in this study was formulated to be:Y = 0.989 + 0,000 GROWTH + 0,0001DPR + e